The dynamics of Islamic values and the pressure of secularism over Islamic schools in TÜrkiye - Susilawati, susilawati; siregar, eliana; Muhammadi, Qasim; Trisasmita, Rio (TA`DIBUNA, 2025)
Foreign Schools aimed at developing Christianity in the Turkish region were visible during the decline of the Ottoman Empire, which had undergone the Reformation. The schools consisted of elementary schools and universities, which were previously intended only for foreign citizens or those considered foreign citizens in the Ottoman Empire. However, this school continued to develop its wings through the Christian mission of various countries, including the United States. After Turkey turned into a republic, there was a secularization of the anti-Islamic education system. Islam is considered an obstacle to progress that has been eroded by time. By conducting a literature study, we took a historical approach with source verification and qualitative data analysis, which was then explained descriptively. We found that Islamic education cannot be stopped because History cannot be erased just like that. The identity of Turkish society comes from Islam. Even though the Islamic values ​​in education in Turkey experienced degradation along with the disbandment of Islamic schools, recently, the Turkish secularist figure Kemal Atatürk died, and Islamic schools gradually re-emerged during Erdogan's reign. More Islamic schools are learning the Koran and Hadith again, using Arabic, which is expected to produce a pious and devout generation.